Lighting Quality Evaluations using Images on a High Dynamic Range Display - NEWSHAM, Guy R.; SEETZEN, Helge; VEITCH, Jennifer A.; CHAUDHURI, Avi; WHITEHEAD, Lorne A. (ARCC Conference Repository, 2019)
Limited research comparing participant ratings of luminous environments to ratings of images of those environments indicates that images can be a reasonable surrogate for the real space, particularly on ratings related to aesthetics. However, the realism of such images when presented on computer screens is potentially limited by conventional display technologies that cannot reproduce the full range of luminances in real spaces. In this pilot experiment we used a new, high dynamic range (HDR) computer monitor capable of producing screen luminances and contrasts comparable to those in a real space. Fifty-four participants viewed three images of a conventional office in two display modes: HDR monitor and conventional monitor. Participants rated each image for room appearance, environmental satisfaction and realism. These ratings were also compared to similar ratings made by participants in an earlier experiment (reported in 1998) who occupied the real spaces depicted in the images. Results indicate that computer screen images are perceived in a similar way as real luminous environments. HDR images are perceived differently than images on a conventional monitor: they are rated as brighter and less attractive, as expected. Given their more authentic luminances, HDR images should be perceived as more similar to the real space, but our results neither support nor refute this.